Kematangan Emosi dengan Penyesuaian Sosial pada Siswa SMP - Alfian Wahyu Sholikah Rahmawati (Nur Science Institute, 2021)
Adjustment and emotion both play a very important role in human life. A person is a social human, who lives in society and faces every condition and situation in their environment (good or bad) from their community. The purpose of this study was to determine the relationship between emotion maturity and social adjustment of Junior High School 1 Students, Sumberlawang, Sragen. The method in this study uses quantitative methods. The research subjects were 85 students with sampling using cluster random sampling techniques. The method of collecting data uses a scale social adjustment and emotion maturity. Data analysis techniques use Product Moment analysis techniques. The product moment calculation results obtained by the correlation coefficient r (XY) = 0.663 with significance = 0,000; (p <0.01), meaning that there is a very significant positive relationship between emotion maturity and student social adjustment. The contribution of emotion maturity effectiveness to social adjustment of students is 66.3%. From the results of this study, it is also known that emotion maturity and social adjustment of students are high.